Creation of vector Bessel beams with arbitrary polarization modes using mode extraction principle - Wang, Lingyu; Sun, Xiaojie; Wang, Guanxue; Kang, Xiangyu; Li, Ziyan; Gao, Xiumin; Zhuang, Songlin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
According to the current research on polarization generation methods, it is difficult to create multi-mode vector Bessel beams in free space by extracting arbitrary polarization modes from a single beam. This is due to the fact that the polarization and phase distributions between multiple polarization modes can interfere with each other. In this paper, the mode extraction principle is combined with the optical pen technique to extract arbitrary polarization modes from a single Bessel beam, and the number, position and phase of Bessel beams can be arbitrarily regulated to achieve the multi-mode coexistence of vector Bessel beams in free space. The experimental results are consistent with the theoretical analysis. This work is not only important for the in-depth study of vector Bessel beams, but also will facilitate the development of optical manipulation, optical communication, microscopic imaging and other applications.
Optica Applicata, Vol. 53, 2023, nr 4, s. 575-589
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; vector Bessel beam; the mode extraction principle; arbitrary polarization modes